Development of service quality dimensions in Malaysia - The case of A multicultural society. - Ting, Lee Hui; Boo, Huey Chern; Othman, Mohhidin (SEGi University College, 2011)
Service quality (SERVQUAL) is now recognized as an integral component of a firm’s customer satisfaction program. Therefore, it is important to understand how consumers perceive the quality of services rend ered, as well as how these perceptions are translated into customer satisfaction and behavioral intentions. Since delivering high SERVQUAL is the cornerstone of any marketing strategy, the marketer must have the means to measure it. Despite the dearth of SERVQUAL studies in the non-Western market in the literature, the SERVQUAL dimensions have failed to receive much attention outside the Western market. This study attempts to examine the SERVQUAL dimensions of those who are concerned with the hospitality and tourism industry in Malaysia.